Solar radiation availability to various collector geometries: a preliminary study - Boes, E. C. (Sandia Laboratories, 1976)
Solar energy collectors of various designs and installation orientations are being built or used. Because most existing solar energy data consists of measurements of total radiation incident upon a horizontal surface, and because geometric conversion to radiation incident upon another surface is difficult, the amounts of solar energy available to various locations are not well known. This paper reports such solar energy availabilities to various collectors for both clear and average days in each of the four seasons at Albuquerque, Blue Hill, and Omaha. Unlike several similar previous studies, the amounts of solar energy given here are based directly on representative data samples consisting of simultaneous measurements of direct-normal and total-horizontal radiation at these three sites.